Possibilities for Change of Thermoplastic Tensile Properties Using Admixture of Recyclable Material - Majerník, Ján; Kmec, Ján; Karková, Monika; Podařil, Martin (Manufacturing Technology Journal, 2017)
Polymeric materials are thanks its processing and utility properties materials in demand of common and special use. They are also largely replacing conventional materials. As the popularity of polymeric materials grows, also the amount of its waste increases. For this reason, there is introduced the term recycling as a method of processing, re-use of the waste, into technologies of polymeric processing. So, this paper deals with the possibilities of introduction of recycled material. The main part of this paper is created by an experiment that explores the changes of tensile properties of test specimen according to the selected percentage of additives in the volume of the basic granulate. The test specimen was produced by mixing pure granules with the addition of recycled and re-granulated materials. The conclusion of this work presents a comparison of the results of each tensile test that provide an overview of the behaviour and properties of the materials tested.
Keywords: thermoplastic; recycled material; tensile test